Actividad en el edificio Paraninfo en la UNED. (UNED, 2024)
De izquierda a derecha de primero Adib Abdallah Arrieta, Delia Feoli Chaves, Don Rodrigo Arias Camacho, Mercedes Mesén Valverde y César Sancho Solís